COMPARISON OF CONGENITAL HEART DISEASE IN INFANTS OF DIABETIC AND NON-DIABETIC MOTHERS (Journal of Medical & Health Sciences Review, 2025)
Objectives: To compare frequency of congenital heart defects in infants of diabetic versus non-diabetic mothers.Study design: Case-control study.Place and Duration of the study: Children Hospital, Pakistan Institute of Medical Sciences, Islamabad from October-2024 to March-2025.Methodology: A total of 390 term neonates born to diabetic (cases) and non- diabetic (controls) mothers were included. All the neonates born to cases and controls were assessed for presence of congenital heart defects by performing echocardiography. Chi-square test was used to compare frequency of congenital heart defects between groups. Data was analyzed using SPSS version 22.Results: Median maternal age was 29.00 (8.00) years. Median gestational age was39.00 (3.00) weeks. There were 139 (35.60%) male and 251 (64.40%) female babies. Median birth weight was 3.50 (0.70) kg. Frequency of congenital heart defect in infants whose mothers were diabetic was 43 (22.05%) while in infants whose mothers were non-diabetic was 20 (10.26%), (p = 0.002); [Odds ratio (OR)= 0.404]. Most common type of congenital heart defect in infants with congenital heart defect whose mothers were diabetic (n = 43) was transposition of great arteries found in 17 (39.53%) infants while in infants with congenital heart defect whose mothers were not diabetic (n = 20), most common congenital heart defect type was ventricular septal defect found in 6 (30.00%) infants, (p = 0.003).Conclusion: Diabetes can contribute to higher chances of developing congenital heart defects in term neonates.